Smart Techniques for a Smarter Planet Towards Smarter Algorithms - Mishra, Manoj Kumar; Mishra, Bhabani Shankar Prasad; Patel, Yashwant Singh; Misra, Rajiv (Studies in Fuzziness and Soft Computing,, 2019)
This book is intended to provide a systematic overview of so-called smart techniques, such as nature-inspired algorithms, machine learning and metaheuristics. Despite their ubiquitous presence and widespread application to different scientific problems, such as searching, optimization and /or classification, a systematic study is missing in the current literature. Here, the editors collected a set of chapters on key topics, paying attention to provide an equal balance of theory and practice, and to outline similarities between the different techniques and applications. All in all, the book provides an unified view on the field on intelligent methods, with their current perspective and future challenges. .